(untitled) (Contemporary Journal of Social Science Review, 2025)
This study presents a comparative phonological analysis of two lesser-documented varieties of the Sindhi language, Aer and Bhaya, both spoken in southeastern Sindh, Pakistan. Grounded in the theoretical framework of Optimality Theory (Prince & Smolensky, 2004), this study investigates how variation between the two varieties influences segmental and suprasegmental phonological features. The objective is to uncover phonemic distinctions based on syllable structures and phonotactic constraints unique to each array, contributing to a broader typological and sociolinguistic understanding of Sindhi dialectology. This study employed a qualitative descriptive research design with a fieldwork-based approach. Primary data were collected through semi-structured interviews and audio recordings of spontaneous speech from 20 native speakers of each dialect, selected using a purposive sampling method. Elicitation techniques included word lists, picture naming, and narrative prompts to ensure a range of phonological environments. All data were transcribed using the International Phonetic Alphabet (IPA) and analyzed using Praat software for acoustic analyses. Preliminary findings indicate notable divergences in vowel inventories, with Bhaya showing diphthongal tendencies, whereas Aer retains monophthongs. Consonantal variations include the presence of retroflex fricatives in Bhaya, which are absent in Aer. Prosodic features also differ; Aer exhibits fixed initial stress, whereas Bhaya allows for variable stress placement depending on the morphological structure. These variations are analyzed in light of markedness and faithfulness constraints within the framework of Optimality Theory. This research contributes to the documentation and preservation of Sindhi varieties in the southeastern regions, highlighting the phonological richness of minority linguistic communities. Moreover, it offers insights into dialectal shifts influenced by geographical isolation and sociolinguistic contact, aligning with recent studies of South Asian linguistic diversity (Shackle, 2018; Zukowski & Waris, 2021).